Analisa Kompor Biomasa Sebagai Pembangkit Listrik Dengan Model 3 Thermoelektrik - Woro Agus Nurtiyanto; Perani Rosyani; Ariyawan Sunardi; Fatakhu naim; Aripin Triyanto (CV. Multi Kreasi Media, 2022)
One of the alternative energy sources with great opportunities to develop its utilization in Indonesia is biomass energy. Biomass energy can be obtained from nature, Indonesia has abundant sources of biomass so that the potential can be used as a very large energy source. Writing this caria aims to describe the use of biomass materials so that they can be useful for the community which is produced for power generation from biomass stoves by utilizing the heat generated. It conducts research using the library method, selecting reference books according to the title, as well as design methods (design procedures) and testing methods (tool testing). From the results of these studies, the results obtained were using 3 different electric thermoelectric modules produced. From the experiments that have been carried out, we can conclude that by using 3 types of thermoelectric the largest time voltage generated from these experiments ranges from 1.5 minutes to 3.5 minutes at a temperature of 970C using a thermoelectric type 27145 and using a heatsink 10, namely the voltage generated by the produce 2 volts in 3 minutes to 3.5 minutes. By generating electricity generated during cooking by utilizing heat that is delivered to the thermoelectric.